Levamisole-associated multifocal inflammatory encephalopathy: clinical and MRI characteristics, and diagnostic algorithm - Fominykh, V.; Averchenkov, D.; Volik, A.; Popova, E.; Bryukhov, V.; Nazarov, V.; Moshnikova, A.; Arzumanian, N.; Tatarenko, A.; Nechaev, V.; Manuylova, O.; Lapin, S.; et al. (Multiple sclerosis and related disorders, 2023)
•LAMIE is an important diagnostic consideration in the demyelinating episode in developing countries.•Only 1/5 of LAMIE patients with specific oligoclonal bands synthesis in CSF convert to multiple sclerosis.•Three MRI LAMIE patterns were described. Levamisole-associated multifocal inflammatory encephalopathy (LAMIE) is a devastating adverse effect of levamisole (LEV) treatment. In Russia, people often use LEV without a doctor's prescription for anthelmintic prophylaxis. LAMIE often misdiagnosed as the first episode of MS or acute disseminated encephalomyelitis (ADEM). The aim of our study was to describe clinical, laboratory and morphological characteristics of LAMIE, magnetic resonance imaging (MRI) patterns and create an algorithm for the differential diagnosis. This study was a prospective observational study with retrospective analysis of cases. It was performed at two hospitals with ambulatory service for MS. We included 43 patients with LAMIE with follow-up was from 1 year to 5 years. Age was 19-68 y.o. with female predominance. The most typical manifestations of LAMIE were cerebellar, pyramidal and cognitive symptoms, and majority of patients had biphasic course of the disease. Three main types of MRI patterns were described: ADEM-like, MS-like, atypical demyelination. About 40% of patients had CSF specific oligoclonal bands synthesis, but only 20 % of them converted to MS during the period from 1 month until 2 years. The CSF albumin levels and immunoglobulin G index were elevated in LAMIE patients compared to reference values. We described results of brain biopsy in two cases. Therefore LAMIE should be considered in patients with demyelinating or inflammatory conditions with biphasic onset of the disease and variable MRI presentation. [Display omitted]